Antioxidant and Antibacterial Potential of Achillea millefolium, Sisymbrium irio and Viola canescens from Azad Jammu Kashmir, Pakistan: Potential of Viola canescens from Azad Jammu Kashmir - Fatima Gorayah; Rida Batool; Rimsha Dilshad (Biological Sciences - PJSIR, 2023)
Utilization of plants to cure different ailments has been in practice from centuries. In current study, evaluation of phytochemical constituents, antioxidant and antibacterial activity of Achillea millefolium, Sisymbrium irio and Viola canescens collected from Azad Jammu and Kashmir was performed. Presence of various phytochemicals was detected in ethanolic extracts of the selected plants. V. canescens extract exhibited maximum antioxidant activity (86%) tested by DPPH (1, 1-diphenyl-2-picryl-hydrazyl) assay phosphomolybdate (526µg/mL) and antibacterial activity against Bacillus (12mm) and Pseudomonas (3mm) strains. Minimum inhibitory concentration (MIC) of V. canescens was found to be 6.25mg/mL. Thin Layer Chromatography (TLC) of V. canescens showed 15 spots and out of these only three spots gave antibacterial activity against Bacillus subtilis strain. GC-MS analysis revealed 2H-1,4-benzodiazepin-2- one, 7-chloro-1,3-dihydro-5-phenyl-1- (trimethylsilyl)-oxy, cyclohexasiloxane, dodecamethyl and octasiloxane hexadecamethyl as bioactive components of Viola canescens. These compounds can be exploited in pharmaceutical sector in place of the synthetic drugs.